REGULATORY COMPLIANCE IN THE DIGITAL AGE: HOW MAINFRAME MODERNIZATION CAN SUPPORT FINANCIAL INSTITUTIONS - Narasimha Rao Vanaparthi (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explains the critical intersection of digital transformation and regulatory compliance in the financial services sector, focusing on the challenges and opportunities presented by mainframe modernization. As financial institutions face increasingly complex regulatory requirements, legacy systems pose significant obstacles to effective compliance management. This article explores how modernization initiatives, particularly through API-first architectures, enhanced data management capabilities, and advanced security features, can address these challenges. Through a detailed case study of HSBC's transformation journey and analysis of implementation strategies, the article demonstrates how systematic modernization approaches can improve regulatory compliance while optimizing operational efficiency. The article further investigates future considerations, including scalability requirements, system flexibility, and the integration of emerging technologies such as artificial intelligence and natural language processing in compliance management.